2015
DOI: 10.1016/j.molonc.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

4‐protein signature predicting tamoxifen treatment outcome in recurrent breast cancer

Abstract: Estrogen receptor (ER) positive tumors represent the majority of breast malignancies, and are effectively treated with hormonal therapies, such as tamoxifen. However, in the recurrent disease resistance to tamoxifen therapy is common and a major cause of death. In recent years, in‐depth proteome analyses have enabled identification of clinically useful biomarkers, particularly, when heterogeneity in complex tumor tissue was reduced using laser capture microdissection (LCM). In the current study, we performed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…Known mechanisms of resistance to hormone therapies are complex and include epigenetic regulation of ESR1 expression [5,6], ESR1 mutations [712], alternative splicing events [3], ESR1 truncation and fusion events [13], post-translational modifications [14,15], alterations in the hormone binding domain [7,16], alter-native recruitment sites within the genome [17], differential recruitment of coregulators [18], feedback loops by ER target genes on expression/activity of ER [19 ● ], downstream actions of ER target genes on growth factor pathways and other signaling networks [20,21 ●● ], influences of the tumor microenvironment [22], and many others (Figure 1). The details of these mechanisms are beyond the scope of this review but have been thoroughly described by others [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Known mechanisms of resistance to hormone therapies are complex and include epigenetic regulation of ESR1 expression [5,6], ESR1 mutations [712], alternative splicing events [3], ESR1 truncation and fusion events [13], post-translational modifications [14,15], alterations in the hormone binding domain [7,16], alter-native recruitment sites within the genome [17], differential recruitment of coregulators [18], feedback loops by ER target genes on expression/activity of ER [19 ● ], downstream actions of ER target genes on growth factor pathways and other signaling networks [20,21 ●● ], influences of the tumor microenvironment [22], and many others (Figure 1). The details of these mechanisms are beyond the scope of this review but have been thoroughly described by others [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It participates in important cell processes such as cell signaling, cell differentiation and apoptosis through regulating bubble aggregation, inflammatory response and the activity of phospholipase A2.More and more evidence shows that,ANXA1 affects cell proliferation, invasion, epithelial-mesenchymal transition [79][80][81][82] and chemoresistance. 39,83,84 ANXA1 is a substrate for protease C and tyrosinase, and possesses multiple calcium-phosphorus binding sites. At its N-terminus, a region similar to the src homology domain can bind the linker protein Grb-2, which regulates multiple signaling pathways, thereby regulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…De Marchi et al used a previously identified four‐protein‐based classifier composed of: programmed cell death protein 4 (PDCD4), cingulin (CGN), Ras GTPase‐ activating protein‐binding protein 2 (G3BP2), and ovarian carcinoma immuno‐reactive antigen domain containing protein 1 (OCIAD1) to assess the prediction of tamoxifen treatment outcomes using 38 breast cancer whole tissue lysates (WTLs) (25 samples from patients with good treatment outcome and 13 samples from patients with poor treatment outcome) by iMRM (MRM coupled with immunoprecipitation). Only PDCD4 and CGN were found to be significantly different between the patients with poor compared to good treatment outcomes.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Only PDCD4 and CGN were found to be significantly different between the patients with poor compared to good treatment outcomes. Furthermore, the 4‐protein signature was assessed in an independent set of 24 patient‐derived immuno‐enriched serum samples before and after tamoxifen therapy: CGN and OCIAD1 were significantly decreased and G3BP2 was significantly increased in their expression levels after tamoxifen treatment, whereas PDCD4 showed no significant change between the two time points …”
Section: Systematic Reviewmentioning
confidence: 99%